"It helped us, and it hurt us" The role of social media in shaping agency and action among youth in post‐disaster Nepal. (9th October 2020) - Dahal, Leena; Idris, Mussa S.; Bravo, Vanessa
Abstract: This case study explores the communication platforms that youth in Nepal used to respond to the Gorkha earthquake that struck this country on 25 April 2015, and it delves into the role that social media played in shaping the relief efforts initialled and led by youth in Nepal. The data were collected through ethnographic fieldwork and 50 in‐depth interviews conducted in Nepal during the summers of 2015 and 2016 with Nepali youth directly involved in the relief efforts during the immediate aftermath. Findings show that Nepali youth served as integral agents of influence in the chaotic aftermath of the Gorkha earthquake, it highlights the various ways in which virtual communities mostly helped but (in some cases) hindered the relief distribution and coordination process, and it analyses how these 50 young people in Nepal conceptualized social media's role in shaping their agency and resilience. Implications are discussed on how the results of this case study can allow academics and practitioners gauge the effectiveness of social media platforms to respond to crises, understand their impact for people in distinct generations and evaluate the feasibility and inclusivity of using social media as a tool in national crises, especially in developing countries.